Karl Polanyi for Historians: An Alternative Economic Narrative - Knowles, Rob; Owen, John R. (The European Legacy, 2008)
The purpose of this essay is to provide the historian with a generic understanding of the term economy by examining some aspects of the work of the Hungarian “economic historian” Karl Polanyi (1886–1964). It does not seek to explain Polanyi's economic ideas to economists nor does it seek to locate his ideas within the discourses of the academic discipline of economics; there is abundant academic literature which carries out those tasks. This essay is intended to help fill a void in the historical understanding, especially the modern historical understanding, of the term economy, and of how the characteristics associated with it are generally understood. Yet, in reality, it is the neoclassical paradigm of economics which is typically and uncritically taken to be the touchstone for understanding the economy. This circumstance is problematic, however, when referring to the economy of societies earlier than the late nineteenth century or of societies whose culture differs radically from that of the advanced capitalist “west.” Polanyi's insights may help historians avoid the risk of either distorting or anachronistically misunderstanding the economy of such societies.
History
Keywords: economic history; economic theory; history

Weber, Polanyi, and Finley - Tompkins, Daniel P. (History and Theory, 2008)
KM: a review article on Nafissi's book.
History
Keywords: WEBER; Max; 1864-1920; biography; review